1997
DOI: 10.1161/01.atv.17.11.2868
|View full text |Cite
|
Sign up to set email alerts
|

Genistein, the Dietary-Derived Angiogenesis Inhibitor, Prevents LDL Oxidation and Protects Endothelial Cells From Damage by Atherogenic LDL

Abstract: There is now growing evidence that the oxidative modification of LDL plays a potential role in atherosclerosis. In this study, genistein, a compound derived from a soy diet with a flavonoid chemical structure (4',5,7-trihydroxyisoflavone), which was found to inhibit angiogenesis, has been evaluated for its ability to act as an LDL antioxidant and a vascular cell protective agent against oxidized LDL. The results showed that genistein was able to inhibit the oxidation of LDL in the presence of copper ions or su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
114
0
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(125 citation statements)
references
References 38 publications
3
114
0
5
Order By: Relevance
“…Moreover, the present study demonstrated that genistein treatment resulted in a decrease in gastric mucosal TBARS, which is considered a good indicator of lipid peroxidation, in the WIR stress model. Since genistein contains a phenol hydroxyl residue and has a potent radical scavenging effect (2,28,29), data from the present experiments indicate that genistein may act as an antioxidant in the gastric mucosa, thereby scavenging ROS in the gastric mucosa.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Moreover, the present study demonstrated that genistein treatment resulted in a decrease in gastric mucosal TBARS, which is considered a good indicator of lipid peroxidation, in the WIR stress model. Since genistein contains a phenol hydroxyl residue and has a potent radical scavenging effect (2,28,29), data from the present experiments indicate that genistein may act as an antioxidant in the gastric mucosa, thereby scavenging ROS in the gastric mucosa.…”
Section: Discussionmentioning
confidence: 64%
“…Isoflavones contains three aglycones: genistein, daidzein, and glycitein. In particular, genistein exerts various effects, including estrogen-like activity ( 1 ), anti-oxidant effects ( 2 ), and an anti-cancer effect ( 3 ). In the gastrointestinal field, genistein has been reported to inhibit activity of Helicobacter pylori , a bacterium that plays a pathophysiologic role in gastritis and gastric ulcer formation ( 4 ).…”
mentioning
confidence: 99%
“…These compounds also inhibit the activity of a number of enzymes (Adlercreutz et al, 1993a;Evans et al, 1995;Makela et al, 1995a). Isoflavones have antioxidant activity (Wei et al, 1995), which in vivo has been shown to reduce the susceptibility of lipids to oxidation (Jenkins et al, 2000;Kapiotis et al, 1997;Ruiz-Larrea et al, 1997;Sheiber et al, 1999;Tikkanen et al, 1998) contributing to the overall cardio-protective effects of soy protein by favorably influencing lipid homeostasis (Anderson et al, 1995;Crouse et al, 1999).…”
mentioning
confidence: 99%
“…O LDL-colesterol retirado de indivíduos que usam proteína de soja, parece ser também mais resistente à oxidação in vitro (56,57) . Foi observada ação antioxidante da quercetina in vitro , o que poderia proteger contra o dano oxidativo ao LDL implicado na aterogênese.…”
Section: Efeitos Em Doença Cardiovascular E Trombofiliaunclassified